2022
DOI: 10.4028/p-zd7k11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Curved Fibers on the Mechanical Behavior of Variable Stiffness Composites

Abstract: Composite materials are widely used in various industries due to their high specific characteristics. The most common composites are laminates, which consist of multidirectional layers with unidirectional fibers adapted to stresses of the laminates. However, the efficiency of such structures is significantly reduced when there are stress concentrators. One of the ways to increase the efficiency of composite structures with stress concentrators is to change the reinforcement structure and use the transition fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Based on cubic NURBS curves, Rouhi et al 6 designed and manufactured a VS cylinder, and their experiment results showed that the buckling resistance of the VS cylinder was about 18.5% higher than that of the CS one. Malakhov et al 7,8 planned the fiber‐tow paths of VS laminates according to the direction of maximum principal stress on each element in FE model, and built a model to predict their ultimate load by taking the heterogeneity of material properties into account. With higher‐order shear theory, Aditya Narayan et al 9 studied the thermo‐elastic buckling characteristics of VS composite shells, namely, cylindrical and spherical shell panels under the action of uniform or non‐uniform thermal load conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on cubic NURBS curves, Rouhi et al 6 designed and manufactured a VS cylinder, and their experiment results showed that the buckling resistance of the VS cylinder was about 18.5% higher than that of the CS one. Malakhov et al 7,8 planned the fiber‐tow paths of VS laminates according to the direction of maximum principal stress on each element in FE model, and built a model to predict their ultimate load by taking the heterogeneity of material properties into account. With higher‐order shear theory, Aditya Narayan et al 9 studied the thermo‐elastic buckling characteristics of VS composite shells, namely, cylindrical and spherical shell panels under the action of uniform or non‐uniform thermal load conditions.…”
Section: Introductionmentioning
confidence: 99%